Аcute cardiac failure during influence A (H1N1) treated with noninvasive ventilation – a case report - Suša, Romana; Ćupurdija, Vojislav; Novković, Ljiljana; Lazić, Zorica; Petrović, Marina; Đokić, Bojan; Ivošević, Anita; Vuleta, Marko; Čekerevac, Ivan (PONS - medicinski časopis, 2017)
64 year old female patient was hospitalized in the intensive care unit of Clinic for Pulmonology, Clinical Center Kragujevac, due to fever, dry cough, dyspnea, fatigue and swelling of lower limbs. The symptoms started abruptly, 4 days before the admittance to the hospital. Upon admission, somnolence and signs of central cyanosis were noted. Auscultatory finding on the lungs was characterized by bilataral inspiratory crackles, while cardiac sound was silent, HR-120/min, TA-110/60mmHg. Analysis of arterial blood gases registered acute respiratory failure: pO2=5.1kPa, pCO2= 9.2kPa, pH=7.45, SAT=62%. Chest X-ray showed bilateral condensations in the lung parenchyma, predominantly in parahilar area. Cardiac shadow was enlarged. Laboratory tests showed increased value of pro-BNP (4086 pg/mL) (reference values: < 125 pg/mL - negative; 125-400 pg/mL - intermediate; > 450 pg/ml – heart failure). Echocardiographic exam upon admittance showed dilated cardiac cavities, global hypokinesis and ejection fraction of 35%. Noninvasive ventilation (NIV) treatment was started (BiLEVEL, IPAP 26cmH2O, EPAP 6cmH2O) at first continuously and then only during the night, with intense cardio-diuretic therapy. On the fifth day of hospitalization, the results of virology analyses confirmed influenza A (H1N1) infection. On the 6th day, gas exchange was normalized, complete radiological regression occurred, as well as normalization of echocardiographic exam finding. Our case shows that influenza A (H1N1) virus infection may be complicated by acute cardiac failure. If started on time, NIV treatment with simultaneous cardio-diuretic therapy, could have a positive impact on the resolution of acute heart failure during H1N1 virus infection.